Tundish Deskulling Waste as a Source of MgO for Producing Magnesium Phosphate Cement-Based Mortars: Advancing Sustainable Construction Materials - Anna Alfocea-Roig; David Vera-Rivera; Sergio Huete-Hernández; Jessica Giro-Paloma; Joan Formosa Mitjans (Resources)
Currently, the cement industry stands as one of the sectors with the most significant environmental impact, primarily due to its substantial greenhouse gas emissions and energy consumption. To mitigate this impact, a roadmap has been followed in recent years, outlining a set of objectives aimed at diminishing the environmental footprint of the construction industry. This research focuses on the development of mortars with different water/cement ratios employing an alternative cement, specifically magnesium phosphate cement (MPC) formulated with secondary sources. The goal of this research relays in developing mortars based on MPC by using waste from the metallurgical industry, named tundish deskulling waste (TUN), as an MgO source. The results revealed the optimal water/cement (W/C) ratio for MPC-TUN mortars production through the assessment of various characterization techniques, which was 0.55. This ratio resulted in the highest compressive strength after 28 days of curing and the formation of a stable K-struvite matrix. Furthermore, it demonstrated the effectiveness of aluminum sulphate in preventing efflorescence caused by carbonates. The development of alternative masonry mortars for application in building materials represents a significant stride towards advancing the principles of a circular economy, in alignment with the objectives laid out in the 2030 roadmap.